An Enhanced Cloud Security Model through Z Formal Method - Mulapnen Haruna, Kassem; Isaac Gungbias, Hosea (Journal of Information Security System and Cyber Criminology Research, 2025)
Cloud computing has changed how people and organizations use technology, allowing them to lower IT expenses, offer more services, and launch new business models. Despite its tremendous advantages, the downside that tends to discourage existing and intending users is the issue of security. Security issues ranging from vulnerability of the cloud systems to threats and attacks imply that users' data and resources are not safe and secure. The security issues of cloud computing systems often stem from the security requirements that are either inadequate or ambiguous, as well as the technique used to collect these requirements for developing cloud systems. To ensure enhanced security for cloud data, this study applies the Z specification technique to cloud security requirements. The Z Word Tool validates these requirements, ensuring completeness, consistency, and correctness. Comparative analysis with existing research highlights this study's novelty in employing Z Word Tool's type checker to verify and validate security requirements schema. The proposed enhanced model offers a robust guide for cloud system developers, achieving superior validation accuracy.